Snow dogs - Kerner, Jordan; Kouf, Jim.; Levant, Brian; Gooding, Cuba, 1968-; Coburn, James; Sisq.̤; Nichols, Nichelle; Greene, Graham, 1952-; Bagalso, Joanna; Walsh, M. Emmet, 1935-; Ackerman, Tom.; Bondelli, Roger; et al. (Burbank, CA : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2002)
When a Miami dentist inherits a team of sled dogs, he's got to learn the trade or lose his pack to a crusty mountain man.
Inspired by Winterdance by Gary Paulsen.
Director of photography, Thomas Ackerman ; editor, Roger Bondelli ; music, John Debney ; costume designer, Monique Prudhomme ; production designer, Stephen Lineweaver.
Cuba Gooding Jr., James Coburn, Sisqo, Nichelle Nichols, Graham Greene, Brian Doyle Murray, Joanna Bagalso, M. Emmet Walsh.
MPAA rating: PG.
VHS.
Closed captioned for the hearing impaired.
Keywords: Sled dogs -- Drama; Sled dog racing -- Alaska; Mushers -- Alaska; Inheritance and succession; Films for the hearing impaired; Feature films; Children's films; Comedy films